Comparison of the serology, transforming ability, and polypeptide composition of human papovaviruses isolated from urine. - Wright, P J (1976)
Four isolates of human papovaviruses (RF, GS, DW, and MG viruses) obtained from the urine specimens of renal allograft recipients in widely separated locations were compared with BK virus. Hemagglutination inhibition tests and plaque neutralization assays showed that all were antigenically related to BK virus. All isolates transformed baby hamster kidney cells, transformation being determined by the ability of the cells to plate in soft agar. Purified preparations of each isolate were iodinated with chloramine T and the polypeptide compositions were compared by electrophoresis of disrupted viruses in polyacrylamide gels containing sodium dodecyl sulfate. The gel patterns of all isolates were similar to that of BK virus. The tryptic digests of two major iodinated virion proteins, VP1 and VP3, were analyzed on an ion exchange column. The peptide patterns of GS, DW, and BK virus were identical; those of RF and MG virus closely resembled the patterns of the above three with only minor differences in some peptides. The results show that the four isolates and BK virus are antigenically closely related, have similar onocogenic potential, and are distinguishable from simian virus 40 and JC virus.